ISLAMIC BANKING STRATEGIC: CASE OF BANK SYARIAH MANDIRI - Dini Arifian (LPPM STAI La Tansa Mashiro, 2013)
This research tries to explore the strategy to increase competitiveness of Bank Syariah Mandiri. The goals of this research are to: 1) to analyse Bank Syariah Mandiri roles and function in the present and the future, 2) to analyse internal factors of Bank Syariah Mandiri for increasing competitiveness; 3) to analyse policies needed for increasing competitiveness of Bank Syariah Mandiri and 4) to formulate Bank Syariah Mandiri strategy to increase competitiveness of Bank Syariah Mandiri. This research was conducted using Qualitative design. The data were taken from relevant literatures (Bank Syariah Mandiri annual reports, textbooks, magazines, and relevant internet information). The research has shown that business strategic suggested by strong commitment of the government. Value creation strategy is the best alternative strategy to increase Bank Syariah Mandiri competitiveness.